Pobres, doentes e desvalidos: o asilo São Vicente de Paulo na Cidade de Goiás - SOUZA, Rildo Bento de (2010)
The Asylum St. Vincent de Paul was established in 1909 in the city of Goiás, built at the initiative of the confreres in the Society of St. Vincent de Paul, which was created in France in the first half of the nineteenth century by Frederick Ozanam in. His goal was to create conferences Charity aimed at material and spiritual assistance to the poor. In Goiás, the ideal found fertile soil, and since 1885 held a number of charities, its members visited the jail and the hospital must provide food, clothing and living several poor who crowded the streets, alleys and villages of the former Vila Boa. To optimize the work, the Vincentians founded asylum, built in hygienic and pleasant place on the outskirts of the city. With the intention to house the indigent, poor, destitute, disabled, abandoned and sick of all sorts, asylum soon became the embodiment of the ideal of charity planted by Ozanam, and showcase for its members. Under the direction of internal Dominican Sisters, asylum has become a sacred space. Over time, several people who did not fit the profile of the inmates, aspired to enter the institution, where those who would watch. Donation of houses, money and aid from the influential people were found loopholes to achieve this intention. Our goal is to understand what accounted for the asylum for the three groups directly involved with it, namely, the Vincentians, the Handicapped, and the Dominican Sisters. Restricting the analysis to areas for these groups, we will analyze the real interests that are behind the construction of the asylum St. Vincent de Paul